Impact of plant practices on operational performance : a statistical analysis of data from a Canadian manufacturing survey. - Huang, Yun Bo. (2008)
Much of current research on how manufacturing contributes to plant success relies upon in-depth case studies and the "intuitive guidance" of experienced individuals. Only a few empirical studies have examined the relationship between manufacturing practices and plant manufacturing capabilities. The results of analysis imply that best plants adopt a set of best practices to achieve plant success. The results also indicate that while usage of many practices can significantly distinguish MS groups from LS groups, there is a difference as to how every practice factor and individual practices contribute to plant performance improvement on the five dimensions. It was found that the quality-related practices are the most important ones for improving quality performance, manufacturing technologies are the most effective practices for improving cost & productivity performance. JIT practices are most effective to reduce inventory, and increase delivery reliability. Employee involvement, training and teamwork practices are very helpful for improving performance along employee relationship dimension.